The Problem of European Security (Czech Journal of International Relations, 1966)
Despite all the tremendous changes, major shifts and new realities that have occurred in the world as a result of the development after the Second World War, Europe still remains to a certain extent in a key position, especially from the point of view of maintaining world peace.